DESIGN AN BUILD SYSTEM FILING LETTER ENTER AND LETTER WEB-BASED EXIT (STUDIES CASE DEPARTMENT OF INFORMATION ENGINEERING ) - Herwan Rahmansyah; Ari Purno Wahyu Wibowo (Jurnal Darma Agung, 2022)
In the era of Globalization Development technology growing very fast, especially computer technology with centralized data in Thing filing document. How ever no all school have complete facilities and infrastructure. Like Faculty of Informatics, Bandung City. While at the filing letter conducted in the form of storage hardcopy document . With existence problem that has been mention, Collection section document felt need for change method management current letter this they use, that is Method used in study this is model method development system namely the Waterfall Model. Design and analysis models that use models UML (Unified Modeling Language) which is language object oriented programming or OOP (Object Oriented Programming). And equipped with a number of report letter sign in and mail out . As for the method research used for complete various the problem that happened is literature, observation , interviews, data and system analysis, system design , program development, program testing , program implementation . because filing letter already stored in the database. Conclusion obtained that the application is very easy and helpful in filing letter sign in and mail this proven from evaluation user to application the with score by 94% who stated more effective and efficient .